2011
DOI: 10.1007/s10620-011-1796-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Marker Levels Before and After Curative Treatment of Hepatocellular Carcinoma as Predictors of Patient Survival

Abstract: Abstract-fetoprotein (AFP) is used as a marker for hepatocellular carcinoma (HCC), which is influenced by hepatitis. Protein induced vitamin K absence or antagonist II (PIVKA-II) is a sensitive diagnostic marker. Changes in these markers after treatment may reflect curability and predict outcome. We conducted an analysis of prognosis in 470 HCC patients who received curative treatments, and examined relationship between changes in AFP and PIVKA-II levels after 1-month of treatment in 156 patients. Subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…They are also useful as indicators of the therapeutic effect upon examination before and after tumor resection or local ablation therapy [17,18,19]. Two reports analyzed the relation between AFP and response and prognosis to sorafenib treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also useful as indicators of the therapeutic effect upon examination before and after tumor resection or local ablation therapy [17,18,19]. Two reports analyzed the relation between AFP and response and prognosis to sorafenib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…α-fetoprotein (AFP) and des-γ-carboxy prothrombin (DCP)] [12,13,14,15,16]. In this regard, the response to therapy and the prognosis for patients with HCC are reported to correlate with changes in AFP (before and after treatment) [17,18,19,20,21]. To our knowledge, however, there is little or no information on the correlation between prognosis and changes in tumor markers and the treatment with sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring sensitive markers such as these might be useful for predicting tumor recurrence after hepatectomy [25,26]. Our previous study showed that changes in PIVKA-II or AFP levels were significantly correlated with prognosis in HCC patients undergoing hepatectomy [11]. In addition to these conventional markers, new biomarkers of HCC have been proposed, [27,28] most of which are HCC specific.…”
Section: Discussionmentioning
confidence: 99%
“…Markers of poor hepatic function and tumor-related factors are significantly associated with tumor recurrence and lower survival [6][7][8]. Our previous study showed that an advanced grade of hepatic fibrosis, hepatitis, postoperative long-term ascites or postoperative levels of alpha-feto protein (a marker of chronic hepatitis) were significantly associated with shorter survival due to carcinoma after hepatectomy [9][10][11]. Deteriorated liver function and co-existing hepatitis would influence tumor progression and subsequent carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] On the contrary, loss of serum AFP early after surgery has been found to predict delayed recurrence and increased survival. 9,10 Degradation of preformed serum AFP requires time, even after complete tumor excision. 11 Although the rate at which AFP changes ought be taken into consideration to establish any clinical correlation, this idea has not been tested extensively in HCC patients undergoing hepatectomy.…”
mentioning
confidence: 99%